PERAN PANCASILA DALAM MENEKAN DISINTEGRASI BANGSA ATAS POTENSI PERPECAHAN PERSATUAN DAN KESATUAN MASYARAKAT - Syarifah Aini; Desi Devrika Devra (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
The purpose of this research is to understand the role of Pancasila in suppressing national disintegration, the causes of national disintegration, and the issues related to national disintegration, as it has been found that the topic of national disintegration is always a hot discussion due to its significant impact that can fragment the unity and cohesion of society as the subjects that form an entity known as a state. This type of research is normative and descriptive in nature, and the approach used is a conceptual approach. The data obtained is from library sources and internet media. The source of data used is secondary data. The data collection technique is literature study. The analysis of this research data is qualitative analysis, and it uses deductive reasoning for drawing conclusions. From the research, the conclusion is obtained that the role of Pancasila in suppressing national disintegration is that Pancasila functions as an ideology; ideology serves to provide